Utilization of labor pain management methods and associated factors among obstetric care givers at public health institutions of East Gojjam Zone, Amhara region, Ethiopia, 2020: a facility based cross - sectional study - Aster Shiferaw; Belsity Temesgen; Nakachew Mekonnen Alamirew; Tejitu Wube; Yichalem worku (BMC, 2022)
Abstract Background Labor Pain is "unpleasant sensory and emotional experience associated with actual or potential tissue damage, affects parturient and fetuses'. Developed countries regularly use obstetric analgesia but in developing countries, including Ethiopia pain is neglected and most women go through painful labor. The study was conducted in public health institutions of East Gojjam Zone; Amhara region, Ethiopia. The aim of this study was to assess utilization of labor pain management methods and associated factors among obstetric care givers in the study setting. Method Facility-based cross sectional study design was carried out in public health institutions of East Gojjam Zone from April 15 to May 15, 2020. Semi Structured questionnaires were used and 305 obstetric care givers were participated. Stratified sampling technique was used. Data was entered by Epi- data version 3.1 and exported to SPSS version 20. Descriptive analysis was done and Bivariate and multivariate logistic regression with 95% CI was used to saw the association of dependent and independent variables at p < 0.05. Result Utilization of labor pain management methods in this study was 48.9%. In Multivariate logistic regression; Professional knowledge [AOR = 2.006, 95% CI = ((1.032-3.898)], availability of drug and equipment [AOR = 2.937, 95% CI= (1.311-6.578)] and allow companionship [AOR = 2.587, 95% CI= (1.322-5.063)] were significantly associated with utilization of labor pain management methods. Conclusion and recommendation This study showed low utilization of labor pain management methods. Adequate knowledge, allow accompany and availability of drug & equipment were factors associated with use of labor pain relief options .so it is important to build knowledge of obstetric care givers, availing drugs and materials and make safe the environment for accompany ship to improving use of labor pain management.